Blendas à base de quitosana e exopolissacarídeos: síntese e aplicação na tecnologia de inoculantes. - REIS, Lucas Silva Abrantes (2020)
The aim of this work was to prepare biopolymers blends from chitosan (CT) and exopolysaccharide (EPS) extracted from Rhizobium tropici UFLA 05-16, and to evaluate them as potential carrier materials for nitrogen-fixing bacteria inoculants, providing nutrients and protecting the latter from environmental stressors, such as the high levels of heavy metals. Freshly CT (% DD = 93,2) was blended with different EPS amounts (50:50; 7:33 and 33:67 w/w), and the obtained blends were characterized by infrared spectroscopy (FTIR), solubility , thermogravimetry (TGA / DTA), 15N-NMR, degree of swelling and pHzpc. From the FTIR spectra, it was possible to characterize the various functional groups present in biopolymers, as well as to attribute the formation of blends by the interaction between the amino group of chitosan and the carboxylic group of EPS (–NH3 +-OOC–). The blend obtained showed greater interaction with water than chitosan, less solubility in acid medium than chitosan and was able to adsorb and desorb micronutrients with Cu(II) and Zn(II). In tests with nitrogen-fixing bacteria, the QE1:2 blend was able to adsorb part of the micronutrients that were in excess, favoring bacterial growth. In the assay with blends QE1:2-Cu(II) and QE1:2-Zn(II), both were able to desorb the micronutrients according to the need of the microorganisms, increasing the colony forming units, but not to a much higher value elevated to the experiment carried out without the presence of these blends.